Imagery Actualization in English Translation of Chinese Classical Prose from the Perspective of Gestalt Theory: -- A Case Study of the English-Version the Peach Colony by Lin Yutang and The Peach Blossom Spring by James Robert Hightower - Pang, Ruxin; Pang, Ruyi (Transactions on Social Science, Education and Humanities Research, 2023)
As a vital means to promote Chinese traditional culture overseas, translation of classics is an integral medium to get more say in the dissemination of Chinese culture internationally. With Chinese classical prose loose in forms but condensed in meanings, its translation is a combination of science and artistry. Gestalt theory has the interdisciplinary nature of translation aesthetics and psychology, which has methodological significance for guiding the overall translation of Chinese classical prose. Attempting to apply the principles of continuity, heterogeneous isomorphism, and closure of Gestalt theory as well as the Gestalt imagery actualization theory proposed by Jiang Qiuxia, this paper analyzes the Gestalt imagery actualization in Taohuayuan Ji and the translators’ psychological mechanism in this process by using the “top-down” and “bottom-up” research methods, so as to promote the scientific and standardized application of Gestalt theory in English translation of Chinese classical prose.